Psychological Test Development: Innovative Behavior at Work for Startup Employee - Andi Supandi Suaid Koentary; Adrian X. Qitana (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2022)
The majority of Indonesia's startup companies failed during the early phase of the company. One factor contributing to this failure is the lack of Innovation brought up by the company. Human resource in the company plays an important role in fostering Innovation. Studies showed employee innovative work behavior is the main factor that drives company innovation. This research aims to construct Innovative Behavior at Work scale that is reliable, valid, have good items and norms for score interpretation purposes. The research subjects were an employee who works in a startup company. The result showed that the scale has high internal consistency, valid, and the items discriminate individual capabilities. The norm used in this scale is within group norms with a standard score of M=10 and SD=3.